2022
DOI: 10.2196/35668
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating User Feedback for an Artificial Intelligence–Enabled, Cognitive Behavioral Therapy–Based Mental Health App (Wysa): Qualitative Thematic Analysis

Abstract: Background Digital mental health apps are rapidly becoming a common source of accessible support across the world, but their effectiveness is often influenced by limited helpfulness and engagement. Objective This study’s primary objective was to analyze feedback content to understand users’ experiences with engaging with a digital mental health app. As a secondary objective, an exploratory analysis captured the types of mental health app users. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 23 publications
1
18
0
1
Order By: Relevance
“…Furthermore, participants with high severity injuries, which are associated with greater psychological morbidity, 35 were also statistically more likely to qualify for the study and use the app for longer than those with less severe injuries. The retention potentially indicates that the app was able to facilitate a supportive space for those with heightened needs, as also indicated by an acceptability study of user reviews for Wysa 26 …”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Furthermore, participants with high severity injuries, which are associated with greater psychological morbidity, 35 were also statistically more likely to qualify for the study and use the app for longer than those with less severe injuries. The retention potentially indicates that the app was able to facilitate a supportive space for those with heightened needs, as also indicated by an acceptability study of user reviews for Wysa 26 …”
Section: Discussionmentioning
confidence: 81%
“…The retention potentially indicates that the app was able to facilitate a supportive space for those with heightened needs, as also indicated by an acceptability study of user reviews for Wysa. 26 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, Wysa has been found to improve mental health outcomes in chronic conditions [ 20 , 21 ], with high engagement and adherence [ 22 ]. It was found that users were able to establish a strong therapeutic alliance with the AI-based conversational agent that was comparable to a human therapeutic bond [ 23 ], further confirming the positive feedback from users [ 24 ]. During the pandemic, Wysa also released 2 tool packs (or intervention packages) named “Health Anxiety” and “Remote Wellness,” which were contextualized to the pandemic.…”
Section: Methodsmentioning
confidence: 78%